Peranan Guru dalam Meningkatkan Prestasi Belajar Siswa Kelas VIII Mata Pelajaran Agama Islam di MTsN 2 Kepulauan Meranti - Saimin (Lembaga Yasin AlSys, 2026)
The development of digital technology requires the optimization of teachers’ roles in improving students’ academic achievement through the use of digital devices in the learning process. This study aims to describe teachers’ roles in improving the academic achievement of eighth-grade students at MTsN 2 Kepulauan Meranti in the digital era. This study employed a qualitative descriptive method involving 25 eighth-grade students and two teachers as data sources. The data were collected through observation, interviews, and documentation and were subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that teachers performed seven roles in improving students’ academic achievement, namely as learning resources, facilitators, mentors, demonstrators, learning managers, motivators, and evaluators. These seven roles were implemented effectively during the learning process and supported improvements in students’ academic achievement within the context of digital-based learning. This study concludes that successful improvement in students’ academic achievement in the digital era is influenced by teachers’ ability to perform their roles in an integrated manner, particularly in facilitating learning, providing guidance and motivation, managing learning activities, and evaluating students’ progress. These findings emphasize the importance of strengthening teachers’ competencies in optimizing the use of digital technology to support an effective learning process.